Enhanced Expression of Pullulanase in Bacillus subtilis by New Strong Promoters Mined From Transcriptome Data, Both Alone and in Combination - Meng, Fanqiang; Zhu, Xiaoyu; Nie, Ting; Lu, Fengxia; Bie, Xiaomei; Lu, Yingjian; Trouth, Frances; Lu, Zhaoxin (Frontiers in Microbiology, 2018)
Pullulanase plays an important role as a starch hydrolysis enzyme in the production of bio-fuels and animal feed, and in the food industry. Compared to the methods currently used for pullulanase production, synthesis by Bacillus subtilis would be safer and easier. However, the current yield of pullulanase from B. subtilis is low to meet industrial requirements. Therefore, it is necessary to improve the yield of pullulanase by B. subtilis. In this study, we mined 10 highly active promoters from B. subtilis based on transcriptome and bioinformatic data. Individual promoters and combinations of promoters were used to improve the yield of pullulanase in B. subtilis BS001. Four recombinant strains with new promoters (Phag, PtufA, PsodA, and PfusA) had higher enzyme activity than the control (PamyE). The strain containing PsodA+fusA (163 U/mL) and the strain containing PsodA+fusA+amyE (336 U/mL) had the highest activity among the analyzed dual- and triple-promoter construct stains in shake flask, which were 2.29 and 4.73 times higher than that of the strain with PamyE, respectively. Moreover, the activity of the strain containing PsodA+fusA+amyE showed a maximum activity of 1,555 U/mL, which was 21.9 times higher than that of the flask-grown PamyE strain in a 50-liter fermenter. Our work showed that these four strong promoters mined from transcriptome data and their combinations could reliably increase the yield of pullulanase in quantities suitable for industrial applications.